2020
DOI: 10.1111/hiv.12960
|View full text |Cite
|
Sign up to set email alerts
|

Where are we with pre‐exposure prophylaxis use in Central and Eastern Europe? Data from the Euroguidelines in Central and Eastern Europe (ECEE) Network Group

Abstract: Pre-exposure prophylaxis (PrEP) for HIV infection is an important intervention for control of the HIV epidemic. The incidence of HIV infection is increasing in the countries of Central and Eastern Europe (CEE). Therefore, we investigated the change in PrEP use in CEE over time. Methods The Euroguidelines in Central and Eastern Europe (ECEE) Network Group was initiated in February 2016 to compare standards of care for HIV and viral hepatitis infections in CEE. Data on access to PrEP were collected from 23 count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…3 Major obstacles for prevention still exist, primarily of an administrative, financial, or legal nature. 14,15 Altogether, a clear mismatch exists between the needs of the populations at risk for HIV and the care available in Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…3 Major obstacles for prevention still exist, primarily of an administrative, financial, or legal nature. 14,15 Altogether, a clear mismatch exists between the needs of the populations at risk for HIV and the care available in Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, two studies from the CEE region showed that the number of countries offering PrEP in the region had doubled-up between 2017 and 2018 and the recent data from ECDC confirms this. 16,23,24 Despite these remarkable improvements in availability of PrEP, there is significant regional variability in access to and use of PrEP even in developed countries where it is fully reimbursed. 12,21,25,26 The most common barriers for access to PrEP were defined as not being reimbursed (68.9%), not being licensed (45.9%) and lack of medical guidelines for PrEP use in a previous study from the CEE region.…”
Section: Discussionmentioning
confidence: 99%
“…A later survey showed that the number of countries with PrEP availability in CEE had doubled up in 2019. 16 PrEP has proved to be effective in reducing new HIV diagnoses by 35% in the UK between 2014 and 2018, 25% in Australia between 2015 and 2019 20 and 58% in San Francisco from 2013 to 2018 and has become the mainstay of HIV prevention globally. [17][18][19] PrEP was not licensed in Turkiye at the time this study was run.…”
Section: Introductionmentioning
confidence: 99%
“…Second-line implications for society recognise possible future shocks in tourist arrivals due to viral infections and the emergence of diseases which will likely include HIV/AIDS and COVID-19. Both have been confirmed as significant future risks and threats to the tourism economy and public health, especially HIV/AIDS, which is recognised as the fourth researched threat in tourism [ 40 , 50 , 51 , 52 ].…”
Section: Delimitations and Limitationsmentioning
confidence: 99%